Elaboración de mapa de riesgo de los pozos horizontales perforados desde el año 2006 al 2007 en el campo fanny del bloque tarapoa para el mejoramiento de los ensamblajes de fondo de la sección intermedia de 12 ¼ - Hermida Reina, Monica Isabel (2009)
This material includes the description and analysis of the problems happened in the horizontal Wells drilling, saving this information within a new tool named Risk Map, which definition is a summary of the aspects, drilling risk and tool used, in order to implant it to propose better designs of assemblies and also to have a data base about this. The Risks Map’s design was done to resume all the current problem during 12.1/4” hole section in horizontal wells of the Fanny field inside the Tarapoa Block and the cause of this problems. The methodology used for understanding the problems was the study and data summary of field, trajectories, parameters drill and tools used in wells with similar lithology. With these data an analysis was done about the problems’ severity founds to propose the action plans to take for optimize the decision about the drill string assemblies to use in the perforation of proposed well MIHR-1H. With the help of visual tools as the Risk’s Maps it is projected to accomplish the target of reduce the cost in the perforation.